TRADISI NAIK AYUN DALAM PERSPEKTIF INTERAKSIONISME SIMBOLIK (STUDI MASYARAKAT ETNIS BUGIS DI DESA PUNGGUR BESAR KABUPATEN KUBU RAYA) - Samsiar Samsiar; Amrazi Zakso; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The research is based on the interaction of Bugis ethnic communities Punggur Besar village Kubu Raya district in the implementation of the naik ayun tradition through symbols. The purpose of this study is to know the perspective of symbolic interactionism on the implementation of the naik ayun tradition in the Punggur Besar village Kubu Raya district. The method used in this research is ethnographic studies. The procedure of data collection used were interviews, observation, and documentation. Data analysis in this research refers to Miles and Huberman on the pattern of activity in the analysis consists of data reduction, data presentation, and conclusion. The technique of the examination the validity of the test data using the credibility that consists of the extension of the observation, triangulation of data sources, triangulation techniques, and reference materials.The research was conducted as much as three times of observation. The results of the research observation of the first and second shows that the response of the citizens in the communication and interaction is very good, but in the implementation of the naik ayun ritual tradition, there are some steps that are not implemented. Therefore, the researchers continued observations of the third. The results of the third observations shows that the communication and interaction of Bugis ethnic communities is also very good.The implementation of the naik ayun ritual tradition is carried out gradually starting from the stage of making the great Jodo cake, until the stage get off the ground. It is proven that the symbols used in the naik ayun ritual tradition as a tool for communicating and intraction for the community in the Punggur Besar village Kubu Raya district. Keywords: Bugis Ethnic Communities, Naik Ayun Tradition, Symbolic Interactionism